The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/pace.12701
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Regurgitation Following Implantation of Endocardial Leads: Incidence and Predictors

Abstract: The incidence of increased TR postendocardial lead placement was 10.0%; this is lower than prior estimates. Predevice RA area and RVSP are predictors of increased TR after lead placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 18 publications
4
57
1
2
Order By: Relevance
“…There was a significant increase in the amount and grade of TR in a paced state compared to when the subjects were using their intrinsic conduction system, without any changes in RV ejection fraction or estimated RV systolic pressure . However, the association between pacing burden and amount of TR has not been demonstrated in other retrospective analyses, and the location of the RV lead in one randomized clinical trial of patients who were pacemaker‐dependent (apical vs septal position) was not found to affect the rates of TR …”
Section: Mechanisms Of Tv Dysfunctionmentioning
confidence: 96%
See 1 more Smart Citation
“…There was a significant increase in the amount and grade of TR in a paced state compared to when the subjects were using their intrinsic conduction system, without any changes in RV ejection fraction or estimated RV systolic pressure . However, the association between pacing burden and amount of TR has not been demonstrated in other retrospective analyses, and the location of the RV lead in one randomized clinical trial of patients who were pacemaker‐dependent (apical vs septal position) was not found to affect the rates of TR …”
Section: Mechanisms Of Tv Dysfunctionmentioning
confidence: 96%
“…Risk factors for device‐related TR appear to include predevice right atrial area and elevated RV systolic pressures, as well as older age, abnormal left ventricular relaxation, and pulmonary hypertension after device implant . Multiple transvalvular leads in the RV has fairly consistently been shown to associate with increased rates of TV dysfunction .…”
Section: Incidence Predictors and Clinical Relevancementioning
confidence: 99%
“…These mechanical factors were reproduced in the subsequent series . More recent studies have identified the predictors that are not directly related to PM leads, such as the age, an enlarged RA or RV, the RV systolic pressure, and mitral valve surgery . However, most prior studies had the common limitation of a cross‐sectional design and insufficient patient numbers and failed to determine the “modifiable” factors.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Prior studies have determined the incidence of TR after a pacemaker (PM) implantation is 7-39%. [7][8][9][10][11][12] This is expected to escalate as the number of devices increases in line with a greater proportion of older people in the overall population. However, despite its growing clinical significance, large clinical data focused on the chronological aspect of TR development with sufficient patient numbers and follow-up information are not available.…”
Section: Introductionmentioning
confidence: 99%
“…Также остаются до конца не ясными частота встречаемо-сти и основные механизмы развития недостаточ-ности ТК после имплантации ЭКС [9,17].…”
Section: Introductionunclassified